Design and development of Fuzzy Expert System for diagnosis of hypertension - Azian Azamimi, Abdullah; Zulkarnay, Zakaria; Nur Farahiyah, Mohammad (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/